A performance indicators system for urban wastewater treatment plants - Quadros, S. (2009)
The use of performance assessment systems (PAS) is an important tool to provide a cost-effective and sustainable management of wastewater treatment plants (WWTP). Despite many PAS have been developed in recent years, important aspects of WWTP evaluation are not yet considered. This paper presents the framework and the overall performance indicators of a PAS developed for urban WWTP.